Prevalence of sensitization to extracts from particular life stages of the saw-toothed grain beetle (Oryzaephilus surinamensis) in citizens of selected suburban areas of Southern Poland. (October 2016) - Jakubas-Zawalska, Justyna; Asman, Marek; Kłyś, Małgorzata; Solarz, Krzysztof
Abstract: Many species of insects are agricultural pests which cause not only economic losses but also allergies in humans. The subject of this study was to identify important antigens from the saw-toothed grain beetle – Oryzaephilus surinamensis [OS]. Sera of 30 patients from a suburban population of Upper Silesia (Southern Poland) were tested for the presence of IgE antibodies to antigens from particular active life stages of OS (larvae, pupae and adults of both sexes). The collected proteins were fractionated by SDS PAGE and identified by Western blot. The patient's antibodies against particular antigens were identified using anti-human anti-IgE monoclonal antibody. The conducted studies showed the existence of many protein fractions for each life stage of OS which give positive reactions with IgE antibodies. The largest number of allergenic potential fractions was shown in females (23 protein fractions) and pupae (22 protein fractions) while smaller amount was shown in larvae (18 protein fractions) and males (14 protein fractions). Majority of the sera (25/30) showed positive reactions to protein fractions 25–29 kDa and 30–34 kDa from pupae of OS. The obtained results may indicate the existence of many protein fractions with an allergenic properties in OS. It also should be stressed that all life stages of this storage insect may provoke allergic reactions in exposed subjects. Highlights: The immunological identification from multiple life stage of the saw-toothed grain beetle is reported. The conducted analysis showed the existence of many protein fractions which give positive reactions with IgE antibodies. The conducted research confirm that every life stage may be associated with allergies.